SUBSTANTIATION OF METHODS FOR ASSESSING ENTERPRISE’S SOCIALLY RESPONSIBLE ACTIVITIES’ EFFECTIVENESS - Medynska, Tetiana (European Science, 2024)
In this chapter approaches to enterprise’s social responsible activity performance evaluators are being reviewed. Methods of quantitative and qualitative assessment of enterprise’s CSR are being presented. Methodology for assessing Enterprise’s socially